Effect of use of GeoGebra on achievement of high school mathematics students - Zulnaidi, Hutkemri; Oktavika, Enny; Hidayat, Riyan (Springer, 2020)
A quasi-experiment was conducted to determine the effects of using the software GeoGebra as teaching aid on the achievement of Form Two students. The experimental study was conducted on 80 Form Two students, 40 of whom comprised the treatment group and 40 formed the control group. Data were analysed using the software ANATES 4 and SPSS 24.0. Significant differences were found in student achievements in relation to the topics of functions and limit functions according to their group type. Research outcomes also showed that teachers and students approved the use of GeoGebra in the teaching and learning of mathematics. GeoGebra can illustrate mathematical concepts and procedures well through visuals and graphs, which considerably aid students in mastering and understanding concepts and procedures pertaining to functions and limit functions. This software is user-friendly and can relieve the teachers’ burden in explaining functions. Even though the use of GeoGebra is time consuming, teaching by using the software can render the students’ learning process increasingly active. Moreover, learning mathematics with the help of GeoGebra allows for an active interaction between teachers and students. This study provides suggestions as interventions for increasing student achievement. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.